Determinants of Outpatient Waiting Time at Lawang Malang Hospital - Ivana Kusuma Widyawati; Silvia Intan Wardani (Jurnal Rekam Medis dan Informasi Kesehatan, 2024)
Patient waiting time is the length of time it takes for patients to obtain health services from registration to entering the doctor's examination room. This study aims to identify the factors that affect the waiting time of outpatients at Lawang Malang Hospital. Using a quantitative design with a cross-sectional approach, the study involved 95 respondents from internal polyclinic patients who were selected through non-probability sampling techniques. Data were collected using questionnaires and analyzed by chi-square test and logistic regression analysis. The results showed that most patients experienced a waiting time of more than 60 minutes, exceeding the Minimum Service Standard (SPM). Of the variables studied, only residence had a significant relationship with waiting time (p-value = 0.0001, AOR = 1.93; 95% CI, 1.16-3.21). Other variables such as education, employment, visit days, and registration methods did not show a significant relationship. The conclusion of this study is that the majority of patients wait more than 60 minutes, and the place of residence has an effect on the waiting time. To remedy this situation, it is recommended that hospitals develop an online registration application that is integrated with doctors' schedules to reduce patient waiting times.